2013
DOI: 10.1371/journal.pone.0057757
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Mas agonist, CGEN-856S, Attenuates Isoproterenol-Induced Cardiac Remodeling and Myocardial Infarction Injury in Rats

Abstract: CGEN-856S is a novel Mas agonist. Herein, we examined the effects of this peptide on isoproterenol (ISO)-induced cardiac remodeling and myocardial infarction (MI) injury. We also sought to determine whether CGEN-856S activates the underlying mechanisms related to Mas receptor activation. Heart hypertrophy and fibrosis were induced by ISO (2 mg·kg−1·day−1) in Wistar rats. After a 7-day treatment period with CGEN-856S (90 µg·kg−1·day−1) or vehicle, the cardiomyocyte diameter was evaluated in left ventricular sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
0
29
0
7
Order By: Relevance
“…Ligand treatment with Ang(1-7) or AVE0991 in MAS-transfected cells couples calcium-independent activation of nitric oxide synthase to the phosphatidylinositol 3-kinase/protein kinase B, AKT pathway (Sampaio Verrilli et al, 2012;Savergnini et al, 2013;Than et al, 2013), or activation of phospholipase A2 (Santos et al, 2003b). Ang(1-7) altered the phosphorylation of MAP kinases (Sampaio et al, 2007a;Zimpelmann and Burns, 2009;Liu et al, 2012;Verano-Braga et al, 2012).…”
Section: Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligand treatment with Ang(1-7) or AVE0991 in MAS-transfected cells couples calcium-independent activation of nitric oxide synthase to the phosphatidylinositol 3-kinase/protein kinase B, AKT pathway (Sampaio Verrilli et al, 2012;Savergnini et al, 2013;Than et al, 2013), or activation of phospholipase A2 (Santos et al, 2003b). Ang(1-7) altered the phosphorylation of MAP kinases (Sampaio et al, 2007a;Zimpelmann and Burns, 2009;Liu et al, 2012;Verano-Braga et al, 2012).…”
Section: Signalingmentioning
confidence: 99%
“…The agonist AR234960 was shown to activate G-protein signaling and the inverse agonist AR244555 selectively inhibited the agonist response as well as the constitutive activity of MAS (Zhang et al, 2012;Tirupula et al, 2014). Remarkably, CGEN-856S is reported to activate calcium and AKT signals (Shemesh et al, 2008;Savergnini et al, 2013). Thus, atypical signaling response suggests functional selectivity of MAS, which allows State of the Angiotensin Receptors interaction with different ligands to activate different signaling pathways, a phenomenon also called biased signaling .…”
Section: Signalingmentioning
confidence: 99%
“…A cyclic Ang(1-7) analog containing a thioether bridge that makes it resistant to enzymatic digestion and a hydroxypropyl-β-cyclodextrin incorporated Ang(1-7) formulation (HP-β-CD/Ang1-7) have been synthesized and shown to be cardioprotective in animal models of myocardial infarction and insulin resistance/type 2 diabetes [61][62][63] (Table). As an alternative to Ang(1-7), nonpeptide agonists of the Mas receptor, for example, the imidazole compound AVE0991, 64 and novel G-protein-coupled receptor activating peptides, for example, CGEN-856S that have high specificity for the Mas receptor, 65 have been shown to lower BP and protect the vasculature and kidneys in animal models of hypertension and CVD (Table). The relative merits of Mas receptor activation versus ACE2 stimulation are being debated, but all agree that randomized controlled trials in humans with hypertension and related CVDs are needed to assess the therapeutic potential of activating the ACE2/Ang(1-7)/Mas receptor axis.…”
Section: Activators Of the Angiotensin-converting Enzyme2/angiotensinmentioning
confidence: 99%
“…It should be pointed out that all the described effects of Ang-(1-7) or AVE0991 in Mas-transfected cells are related to a Ca 2+ -independent activation of nitric oxide synthase (via the phosphatidylinositol 3-kinase/protein kinase B [AKT] pathway) or to activation of phospholipase A 2 Pinheiro et al, 2004;Sampaio et al, 2007b;Savergnini et al, 2013;Than et al, 2013) (Fig. 4).…”
Section: A Masmentioning
confidence: 99%
“…1 mM), such as the agonists MBP7 (Bikkavilli et al, 2006), AR234960 , and CGEN-856S (P61 in Shemesh et al, 2008) with serine instead of cysteine (Savergnini et al, 2010), and the inverse agonist, AR244555 . Interestingly, CGEN-856S has been shown to activate both pathways, Ca 2+ and AKT-but Ca 2+ only in Ga16 transfected cells with a diverted signaling (Shemesh et al, 2008;Savergnini et al, 2013). Thus, the still limited evidence about Mas signaling suggests that Mas behaves like other GPCRs, for which it has also been shown that different ligands activate different signaling pathways, a phenomenon called functional selectivity or biased signaling (Urban et al, 2007;Kenakin and Christopoulos, 2013) (Fig.…”
Section: A Masmentioning
confidence: 99%